2014
DOI: 10.1136/jmedgenet-2014-102486
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifiesSLC17A9pathogenic gene in two Chinese pedigrees with disseminated superficial actinic porokeratosis

Abstract: The result identified SLC17A9 as another pathogenic gene for DSAP, which suggests a correlation between the aberrant vesicular nucleotide transporter and the pathogenesis of DSAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…) and disseminated superficial actinic porokeratosis (DSAP) (Cui et al . ). Our study may also help to uncover the molecular mechanisms underlying vesicular ATP release in keratinocytes and the pathogenic mechanisms for DSAP, although further studies are needed to confirm the identity of the vesicles.…”
Section: Discussionmentioning
confidence: 97%
“…) and disseminated superficial actinic porokeratosis (DSAP) (Cui et al . ). Our study may also help to uncover the molecular mechanisms underlying vesicular ATP release in keratinocytes and the pathogenic mechanisms for DSAP, although further studies are needed to confirm the identity of the vesicles.…”
Section: Discussionmentioning
confidence: 97%
“…Porokeratosis encompasses a group of keratinization disorders characterized by circular or annular skin lesions with a distinct hyperkeratotic rim termed the cornoid lamella (Sertznig et al, 2012). Known causative genes are MVD, MVK, PMVK, FDPS, and SLC17A9 (Cui et al, 2014;Zhang et al, 2012;Zhang et al, 2015). Clinically, porokeratosis is classified based on the lesional skin distribution.…”
Section: Introductionmentioning
confidence: 99%
“…3 Beside the mutations in the mevalonate pathway genes MVK, PMVK, MVD and FDPS, 1,4 mutations in SSH1, SART3 and SLC17A9 have also been suggested to be responsible for DSAP. [5][6][7] However, it is suspected that SSH1 is probably not causal to DSAP for it is not confirmed in other previous studies. While in the current study we reported two novel mutations of SSH1 in 1 familial and 1 sporadic Chinese DSAP patient, and immunohistochemical analysis of anti-Slingshot homolog 1 antibody in one typical patient.…”
mentioning
confidence: 74%